Influence of cyber-victimization and other factors on depression and anxiety among university students in Bangladesh - Tareq Rahman; Md. Mahin Hossain; Nurun Nahar Bristy; Md. Zahidul Hoque; Md. Moyazzem Hossain (BMC, 2023)
Abstract Background and objectives Cyber-victimization is closely linked with mental health problems such as anxiety, depression, etc., and has become a growing concern among university students in Bangladesh. In the era of globalization, smart gadgets, the internet, and other online resources are readily available, and these tools and devices have now become the primary method for cyberbullying. The authors aim to explore the impacts of cyber-victimization and other factors on anxiety and depression among university students in Bangladesh. Methods The primary data for this cross-sectional study were collected using a well-structured questionnaire. This study employs three widely used scales such as cyberbullying inventory, general anxiety disorder-7 (GAD-7), and patient health questionnaire-9 (PHQ-9). Descriptive statistics and multivariable logistic regression analyses are carried out to identify the factors associated with depression and anxiety among university students in Bangladesh. Results Findings depict that the prevalence of depression and anxiety among university students was 52.5% and 44.0%, respectively. Depressed respondents were considerably more likely to have difficulty sleeping (p < 0.001), spend more time on social media (p = 0.002), have suicidal thoughts (p < 0.001), and have a high cyber-victimization score (p < 0.001) compared to non-depressed respondents. In comparison with non-anxious respondents, anxious respondents were significantly more likely to: have sleeping difficulties (p < 0.001); spend more time on social media (p = 0.031); have suicidal thinking (p < 0.001); and have a comparatively high cyber-victimization score (p < 0.001). Multivariable logistic regression analysis identified that a one-unit increase in the cyber-victimization score results in a 1.24 times higher chance of experiencing depression (AOR: 1.24, 95% CI 1.17-1.31, p < 0.001), and a one-unit increase in the cyber-victimization score results in a 1.23 times higher chance of experiencing anxiety (AOR: 1.23, 95% CI 1.17-1.30, p < 0.001). Conclusion University students are struggling with cyberbullying, which can lead to depression and anxiety levels. Promoting more cyberbullying awareness is necessary since failing to do so could result in a sustained or increased prevalence of anxiety and depression levels among students, which could have disastrous repercussions.